Answer:
D. -9
Step-by-step explanation:
![5f - 6f = 9 \\ - f = 9 \\ f = - 9](https://tex.z-dn.net/?f=5f%20-%206f%20%3D%209%20%5C%5C%20%20-%20f%20%3D%209%20%5C%5C%20f%20%3D%20%20-%209)
Answer:
gduduufufj jeuyeyrhfi garewhkod ishstdkgo
Answer:
let the of bag of vendors be X
3donate X bag to give 996
3×x=996
3x=996
divide both side by 3
3x\3=996\3
x=332
each vendor donated 332bags of popcorn
<h3>f(x) = -3·2^(x-1) -1</h3>
- reflection across the x-axis (multiplication by -1)
- vertical expansion by a factor of 3 (multiplication by 3)
- shift to the right 1 unit (replace x with x-1)
- shift down 1 unit (add -1 to the function value)
_____
<h3>f(x) = -1/4·2^(x+1) -1</h3>
You may notice this is the same as the previous question, but with the vertical expansion factor 1/4 instead of 3, and the horizontal shift left instead of right.
- reflection across the x-axis (multiplication by -1)
- vertical compression by a factor of 4 (multiplication by 1/4)
- shift to the left 1 unit (replace x with x+1)
- shift down 1 unit (add -1 to the function value)
Answer:
x = i and x = i![\sqrt{5}](https://tex.z-dn.net/?f=%5Csqrt%7B5%7D)
Step-by-step explanation:
Given
+ 6x² + 5 = 0
Using the substitution u = x², then
u² + 6u + 5 = 0 ← in standard form
(u + 1)(u + 5) = 0 ← in factored form
Equate each factor to zero and solve for u
u + 1 = 0 ⇒ u = - 1
u + 5 = 0 ⇒ u = - 5
Convert solutions back into terms of x
x² = - 1 ⇒ x =
= i
x² = - 5 ⇒ x =
= i![\sqrt{5}](https://tex.z-dn.net/?f=%5Csqrt%7B5%7D)